Raising sustainability awareness and understanding in higher education - Erika Graf (Frankfurt University of Applied Sciences, Frankfurt Research Institute for Business and Law, 2015)
Sustainability has been defined by the Brundtland Commission (Brundtland, 1987) as "meeting the needs of the present without compromising the ability of future generations to meet their own needs". In times of increasing expectations of customers, shareholders, employees, and communities as well as the general public about corporations' contributions to sustainability (WBCSD - World Business Council for Sustainable Development), the latter are severely and continuously criticized for actions that contradict their glossy sustainability reports (Holliday, 2010). However, it is often the case that such criticism is rooted in a lack of awareness of the complexity of relationships and the role that sustainability plays within the context of a firm's operations, particularly SMEs, which cannot dedicate major resources to cope with the issues. Therefore, the question arises of what universities can do to build awareness and understanding among students in order to prepare them to cope with sustainability aspects in their future careers (Starik et al., 2010). This paper presents findings based on quantitative and qualitative data from five consecutive crossfunctional courses in sustainability for students in business, law, architecture, health management and engineering, and evaluates the extent to which their attitude and awareness changed over the course. Recommendations are given for institutions in higher education as well as for companies to follow up with further training initiatives for junior managers.
Keywords: 330; sustainability; education; corporate social responsibility; ethics; cross-functional learning